XX amžiaus Lietuvos bibliofilai: J. Kirlys, V. Burkevičius, P. Jakštas - Baltronaitė, Jurgita (Knygotyra, 1998)
Bibliophilia is the important part of the national culture, but the history of Lithuanian bibliophilia was not studied enough yet. In this work the activity of three book collectors of XX century - Jonas Kirlys, Vilhelmas Burkevičius and Petras Jakštas - is examined. The analysis of activity of these book collectors confirms the supposition that the character of their activity reflects basic tendencies of 20th century bibliophilia. Their work was influenced by complicated and contradictory conditions of Lithuanian political and cultural life. J. Kirlys, V. Burkevičius, P. Jakštas, as well as other bibliophiles, collected their libraries in two stages, because their first book sets were lost or suffered during the First and Second World Wars. Later these bibliophiles made up significant specialized book collections, that reflected professional and personal interests of its owners. J. Kirlys, V. Burkevičius and P. Jakštas are characterised by diverse bibliophile activity: they analyzed Lithuanian press and bibliophilia history, V. Burkevičius and P. Jakštas were members of bibliophile organization "XXVII knygos mėgėjų draugija", J. Kirlys arranged exhibitions of Lithuanian periodical press, established the first Lithuanian Press Museum. The bibliophiles registered their books, they had their own book signs. The collections of J. Kirlys, V. Burkevičius and P. Jakštas are scattered. Only complete description of the funds of private libraries would give the rich material for the history of the bibliophilia in Lithuania.